MR Enterography Crohn$1 (Bs Disease and Beyond /s - Mazziotti, Silvio; Blandino, Alfredo; Cicero, Giuseppe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This second edition is primarily dedicated to MR-Enterography, an imaging modality whose reliability for intestinal assessment in patients suffering from inflammatory bowel diseases has gained increasing consensus. The performance of this technique has been significantly enlarged over the last years, due to its undoubted advantages in terms of exhaustive evaluation of the abdominal cavity and safeness due to the lack of radiation exposure. The first part is focused on MR-Enterography standard protocol. Nevertheless, additional sequences, technical novelties and common pitfalls are reported and discussed. In the second section, the typical intestinal and extra-intestinal findings related to Crohn$1 (Bs disease are described in detail. In this edition, more emphasis has been put on practical topics, useful in the daily clinical practice: anatomical changes after surgical procedures, structured reporting and emerging clinical applications over inflammatory bowel diseases. Another part is dedicated to Magnetic Resonance Imaging of the anal canal, including technical aspects and clinical implications. The text is largely complemented by diagnostic images. Nonetheless, at the end of the book 30 illustrated cases show different clinical scenarios evaluated with MR-Enterography and Magnetic Resonance Imaging of the anal canal.s
Chapter 1) Introduction -- Chapter 2) Small Bowel Imaging -- Chapter 3) MR Enterography: Technique -- Chapter 4) MR Enterography: Anatomy -- Chapter 5) MR Enterography: Intestinal Findings In Chron$1 (Bs Disease -- Chapter 6) Exraintestinal Complications in Crohn's Disease: MR-Enterography Findings -- Chapter 7) MR Enterography beyond Crohn's Disease -- Chapter 8) MR Enterography Pitfalls -- Chapter 9) MRI of the Anal Region in Crohn's Disease -- Chapter 10) Structured Reporting -- Chapter 11) Clinical Cases.s
Keywords: Radiology; Nuclear magnetic resonance; Gastroenterology; Endoscopy; Pediatrics; Surgery; Radiology; Magnetic Resonance (NMR, EPR).; Gastroenterology; Endoscopy; Pediatrics; Surgery; Magnetic Resonance Imaging -- methods; Intestinal Diseases -- diagnostic imaging; Crohn Disease -- diagnostic imaging; Intestine, Small -- pathology